A Novel Methodology for Economical Scale-Up of TiO2 Nanotubes Fabricated on Ti and Ti Alloys. (3rd March 2019) - Khaw, Juan Shong; Curioni, Michele; Skeldon, Peter; Bowen, Christopher R.; Cartmell, Sarah H.
Abstract : The prospective use of nanotechnology for medical devices is increasing. While the impact of material surface nanopatterning on the biological response is convincing, creating a large surface area with such nanotechnology remains an unmet challenge. In this paper, we describe, for the first time, a reproducible scale-up manufacturing technique for creating controlled nanotubes on the surfaces of Ti and Ti alloys. We describe an average of approximately 7.5-fold increase in cost and time efficiency with regards to the generation of 20, 50, and 100 nm diameter nanotubes using an anodisation technique. These novel materials have great potential in the medical field through their influence on cellular activity, in particular, protein absorption, focal adhesion, and osteoinduction. In this paper, we provide a step-by-step guide to optimise an anodisation system, starting with design rationale, proof of concept, device upscaling, consistency, and reproducibility check, followed by cost and efficiency analysis. We show that the optimised device can produce a high number of anodised specimens with customisable specimen shape at reduced cost and time, without compromising the repeatability and consistency. The device can fabricate highly uniform and vertically oriented TiO2 nanotube layer with desired pore diameters.